The effect of amorphous calcium phosphate on protein protection against thermal denaturation1. Issue 41 (21st May 2015) - Yang, Yuling; Wang, Guangchuan; Zhu, Genxing; Xu, Xurong; Pan, Haihua; Tang, Ruikang
<x xml:space="preserve">Abstract</x> The amorphous calcium phosphate can maintain a stable semi-aqueous nanoscale environment for encapsulated catalase to significantly improve its thermal stability.